Biomechanics of double poling in paralympic cross-country skiing - A cross-sectional study comparing the standing and sitting positions in healthy male subjects - Sasadai, J.; Maeda, N.; Morikawa, M.; Komiya, M.; Shimizu, R.; Fukui, K.; Yoshimi, M.; Kono, Y.; Urabe, Y. (Medicina, 2022)
Background and Objectives: Double poling is an important fundamental skill required for cross-country skiing in able-bodied athletes and in those with physical disabilities. Meanwhile, the performance improvement and injury prevention related to double poling requires a thorough assessment, whereas the scapular and shoulder kinematics in different postural conditions remain to be clarified. The main purpose of this study was to evaluate the biomechanics during cross-country ski double poling in the standing and sitting positions. Materials and Methods: Eleven participants underwent kinematic assessments of the shoulder girdle during double poling on a ski ergometer with an electromagnetic tracking device. The cycle rate, stroke length, stroke speed, thorax motion relative to pelvis, scapular motions relative to thorax, humeral motions relative to thorax, and humeral motions relative to scapula were calculated for five double-poling cycles. Results: In the sitting position, the angles of humerothoracic elevation were 18 degrees larger and glenohumeral elevation 13 degrees larger than in the standing position at the upward point and range of motion. Conclusions: The study revealed that double poling in the sitting condition increased the humerothoracic and glenohumeral elevation angle to secure the poling margin. If these are excessive, there is a risk of shoulder injuries such as subacromial impingement.